FAKTOR-FAKTOR KEUNGGULAN BERSAING DAN IMPLIKASI TERHADAP KINERJA PERUSAHAAN (Studi Kasus UKM Pengelola Ikan Lele di Kabupaten Cirebon) - Gunawan, Wely Hadi; miyasto, miyasto; Susilo, Rahardjo Toto (Indonesian Journal of Strategic Management, 2018)
ABSTRACTSmall and Medium Enterprises (SMEs) are an important part for the community. Matters relating to the performance of SMEs should be noted by research.Based on the data released by the Koperasi Pembudidayaan Lele Mandiri Cirebon regency addressing SMEs decreased production of catfish annual management throughout the year from April to July 2015 through March to June 2016. Therefore, this study was conducted to determine how improve the performance of the company from the SME management of catfish in the district of CirebonThis research was conducted by analyzing the factors that influence entrepreneurial orientation with variable market orientation and competitive advantage variable as an intervening variable. This study develops a theoretical model based stuctural Equation Model (SEM) were tested using Amos 1.8 as an analytical tool. , Respondents of this study is SMEs Lele Cirebon regency totaling 120 people.The results of this study show that entrepreneurial orientation positive effect on company performance, market orientation positive effect of competitive advantage, superiority positive effect on the company's performance, entrepreneurial orientation does not affect the competitive advantage, market orientation does not affect the performance of the company, due to the very short time researchers distributing questionnaires that many respondents could not be interviewed in depth.